Biomechanics in figure skating - Cabell, L.; Bateman, E. (The science of figure skating, 2018)
When a skater executes a triple-triple with technical mastery or perfectly centers a spin with speed and control, most people watching are drawn tothe aesthetic majesty of the sport. What often goes unnoticed are the essential tenets of science that have been identified and integrated into figure skating. During every nanosecond of a skater's movement, a parallel ability of the body to generate and respond to a variety of forces is at play. Biomechanics applies the laws of physics and mechanics to the movement of living organisms - including the execution of every element performed during figure skating programs. lt is a powerful tool used to objectively observe, evaluate, and correct movement to improve performance, reduce injury risk, or during rehabilitation from an injury. Biomechanics is a broad science with many sub-disciplines, and to effectively integrate this tool into best practices, practitioners should have a fundamental knowledge of structural anatomy, kinematics, and kinetics. While it is beyond the scope of this chapter to offer a comprehensive discussion of all things related to biomechanics, the content in this chapter will show how biomechanics influences figure skating. Specifically, the aims of this chapter are to provide a general foundation of basic biomechanical concepts, then demonstrate how these concepts are applied to figure skating. Ultimately, the benefit will be to see how the various sport-specific skills and elements integral to figure skating are achieved through the lens of biomechanical principles.